Diagnostics and treatment of a severe humoral rejection after liver transplantation: donor-specific antibodies as a still underestimated cause of graft failure - Rashidi-Alavijeh, J.; Heinold, A.; Willuweit, K.; Baba, H. A.; Horn, P. A.; Paul, A.; Witzke, O.; Gerken, G.; Herzer, K. (Zeitschrift für Gastroenterologie, 2016)
Background: Donor-specific antibodies (DSAs) are increasingly being considered a cause of complications after liver transplant (LT). However, neither monitoring of DSAs nor the appropriate therapeutic procedures for humoral graft damage are yet standardized. Here we report a case of DSA-positive humoral rejection after LT that was successfully treated with plasmapheresis and immunoglobulins.Methods: Human leukocyte antigen (HLA)-specific DSAs were detected by Luminex bead assay. Patient characteristics, laboratory values, and data about the patient’s general condition were documented from April 2013 to June 2015.Case report: Eighteen months after LT, a 54-year-old man experienced severe hepatopathy with rapidly increasing transaminase activity and total bilirubin levels. Histologic findings were inconclusive, demonstrating chronic cholestasis and minimal positive staining for C4 d. However, an analysis for anti-HLA antibodies detected DSAs against HLA class II molecules with high mean fluorescence intensity. The patient underwent 8 courses of plasmapheresis, resulting in sustained amelioration of his condition and decreases in bilirubin levels and transaminase activity.Conclusion: De novo DSAs can be responsible for graft failure after LT. Thus, procedures aimed at detecting DSAs are recommended, and regular monitoring of DSAs after LT is important for individualized risk management. Plasmapheresis is an efficient therapeutic procedure for DSA-associated graft failure.
Keywords: Lebertransplantation; donorspezifische Antikörper; humorale Abstoßung; Plasmapherese